'Engaging Families to Engage Students' : Exploring how university outreach activities can forge productive partnerships with families to assist first-in-family students navigate their higher education journey : final report. - O'Shea, Sarah (Australia, Dept of Education and Training (DET), 2017)
Final report of a Teaching Fellowship at the University of Wollongong. This Fellowship focused on those students who are the first in their families to come to university, in order to explore approaches to retaining and engaging this cohort. Of particular interest was the ways in which the family and community of learners might be included in this university journey. The project sought to develop a range of resources and deliverables that would connect with both individual learners and their family or broader community.